PERILAKU PENGGUNAAN “QRIS BRI BRIMO” PADA PEDAGANG SEBAGAI ALAT TRANSAKSI PEMBAYARAN DIGITAL - Praditya Wibowo; Santi Rimadias (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- This study aims to analyze the behavior of using "QRIS BRI BRIMO" at merchants as a means of digital payment transactions in Indonesia. This study uses a descriptive research design approach with empirical data collected through an online survey of 100 merchants who adopt "QRIS BRI BRIMO" as a means of digital payment transactions. Data was collected using an online questionnaire from May to August 2022. Empirical data was then processed using the Structural Equation Model Partial Least Square (SEM PLS) to test some of the hypotheses proposed. The results of the study explained that Behavioral Intention proved to have a positive effect on Use Behavior, but Facilitating Conditions proved to have no effect on Use Behavior. Effort Expectations and Social Influence have been shown to have a positive effect on Behavioral Intentions, whereas Attitudes, Performance Expectations, and Facilitation Conditions have been shown to have no effect on Behavioral Intentions. In addition, Trust and Effort Expectations have been shown to have a positive effect on Attitudes, but Performance Expectations have been shown to have no effect on Attitudes. The implications of this research become a reference for the banking industry in designing a payment system in the form of the QRIS feature as a means of digital payment transactions. Keywords: QRIS; Trust; Attitude; Behavioral Intention; Use Behaviour.